Antidyskinetic Effects of MEK Inhibitor Are Associated with Multiple Neurochemical Alterations in the Striatum of Hemiparkinsonian Rats - Chen, Guiqin; Nie, Shuke; Han, Chao; Ma, Kai; Xu, Yan; Zhang, Zhentao; Papa, Stella M.; Cao, Xuebing (Frontiers in Neuroscience, 2017)
L-DOPA-induced dyskinesia (LID) represents one of the major problems of the long-term therapy of patients with Parkinson's disease (PD). Although the pathophysiologic mechanisms underlying LID are not completely understood, activation of the extracellular signal regulated kinase (ERK) is recognized to play a key role. ERK is phosphorylated by mitogen-activated protein kinase kinase (MEK), and thus MEK inhibitor can prevent ERK activation. Here the effect of the MEK inhibitor PD98059 on LID and the associated molecular changes were examined. Rats with unilateral 6-OHDA lesions of the nigrostriatal pathway received daily L-DOPA treatment for three weeks, and abnormal involuntary movements (AIMs) were assessed every other day. PD98059 was injected in the lateral ventricle daily for 12 days starting from day 10 of L-DOPA treatment. Striatal molecular markers of LID were analyzed together with gene regulation using microarray. The administration of PD98059 significantly reduced AIMs. In addition, ERK activation and other associated molecular changes including ΔFosB were reversed in rats treated with the MEK inhibitor. PD98059 induced significant up-regulation of 418 transcripts and down-regulation of 378 transcripts in the striatum. Tyrosine hydroxylase (Th) and aryl hydrocarbon receptor nuclear translocator (Arnt) genes were down-regulated in lesioned animals and up-regulated in L-DOPA-treated animals. Analysis of protein levels showed that PD98059 reduced the striatal TH. These results support the association of p-ERK1/2, ΔFosB, p-H3 to the regulation of TH and ARNT in the mechanisms of LID, and pinpoint other gene regulatory changes, thus providing clues for identifying new targets for LID therapy.